In the way: perpetuating land dispossession of the indigenous Hai//om and the collective action law suit for Etosha National Park and Mangetti West, Namibia. (1st March 2019) - Koot, Stasja; Hitchcock, Robert
Abstract : As former mobile foraging peoples, the indigenous Hai//om San of Namibia lost most of their land - including Etosha National Park and Mangetti West - to other groups and the state in the nineteenth and twentieth centuries. After independence (1990), the government redistributed some of this land to various expropriated groups. In the following overview, we delve into this complex history to argue that the recent decision by the Hai//om (2015) to file a collective action lawsuit against the government of Namibia over Etosha and Mangetti West must be seen in a context of ongoing, often subtle, processes of land dispossession simultaneously taking place as a result of marginalisation and structural disempowerment.